The Influence of TikTok Content on the Purchase Decisions of Customers in Indonesian Skincare Industry - Audrey Finanta (Jurnal Visi Manajemen, 2025)
TikTok has emerged as one of the most influential social media platforms, forming a global online community that penetrates diverse industries, including skincare. In Indonesia, skincare ranks among the most discussed topics on TikTok, which makes the platform a significant channel for influencing consumer behavior. This study aimed to analyze how TikTok content shapes consumer purchasing decisions for skincare products in Indonesia. A qualitative method was applied using in-depth interviews with 12 respondents representing young adult consumers familiar with skincare products. The findings highlight several insights. First, TikTok content positively influences the problem recognition stage, helping consumers become more aware of their skincare needs. Second, TikTok was identified as the second most used social media source for skincare-related information, though its credibility is perceived only at a moderate level. Third, the platform plays a moderate role in the evaluation of alternatives, where consumers compare and consider skincare products. However, nearly half of the respondents reported a gap between information obtained from TikTok and actual product performance, resulting in disappointment and reluctance to share their experiences on the platform. Moreover, respondents revealed clear preferences regarding content: (1) comparative content showcasing product performance, (2) detailed content discussing product features, and (3) content providing tangible proof of effectiveness. These findings emphasize the dual role of TikTok as both an influential information source and a platform with credibility challenges. The study contributes to a better understanding of digital consumer behavior in Indonesia’s skincare industry. It also provides practical recommendations for marketers to design more transparent, credible, and consumer-oriented TikTok marketing strategies.